2015
DOI: 10.1016/j.endoen.2015.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cross-sex hormone treatment on cardiovascular risk factors in transsexual individuals. Experience in a specialized unit in Catalonia

Abstract: Background and aims: Since the onset of cross hormone therapy (CHT) in transsexual individuals, there has been concern about possible chronic side effects. Our objective was to assess baseline differences in lipid profile in individuals with gender identity disorder in relation to prior CHT, and changes in the lipid profile and other cardiovascular (CV) risk factors after 24 months of treatment. Methods: Retrospective longitudinal study including all individuals assisted for the first time in the Gender Identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 17 publications
(15 reference statements)
2
9
0
Order By: Relevance
“…The prevalence of smoking was high in the five studies that reported this cardiovascular risk factor: 37% (Mueller et al ., ), 30% (Chandra et al ., ), 51% (Pelusi et al ., ), 20% (Wierckx et al ., ), and 60% (Quirós et al ., ). Slight but significant increases in BMI were observed in most studies, ranging from 1.3 to 11.4%, during testosterone treatment (Table ).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…The prevalence of smoking was high in the five studies that reported this cardiovascular risk factor: 37% (Mueller et al ., ), 30% (Chandra et al ., ), 51% (Pelusi et al ., ), 20% (Wierckx et al ., ), and 60% (Quirós et al ., ). Slight but significant increases in BMI were observed in most studies, ranging from 1.3 to 11.4%, during testosterone treatment (Table ).…”
Section: Resultsmentioning
confidence: 97%
“…After this step, three articles were excluded because the variables of interest were not reported, and one because a progestin was added to androgen treatment. Thirteen articles were thus included in the systematic review (Giltay et al ., ; Berra et al ., ; Jacobeit et al ., , ; Mueller et al ., , ; Chandra et al ., ; Cupisti et al ., ; Pelusi et al ., ; Wierckx et al ., ; Deutsch et al ., ; Quirós et al ., ; Fisher et al ., ).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…One of the most prominent changes seen in the routine laboratory monitoring of trans persons is a change in hematocrit and hemoglobin: a decrease in trans women (Schlatterer et al ., ; Roberts et al ., ; Quirós et al ., ; Tack et al ., ) and an increase in trans men (Schlatterer et al ., ; Jacobeit et al ., ; Chandra et al ., ; Mueller et al ., ; Pelusi et al ., ; Quirós et al ., ; Jarin et al ., ). As in hypogonadal men on testosterone treatment, the induction of erythrocytosis in trans men on testosterone treatment is of concern because it might be associated with an elevated thrombotic risk.…”
Section: Introductionmentioning
confidence: 99%